O diário de aula como ferramenta motivacional para a formação docente de estudantes do curso de pedagogia, participantes do PIBID - Rodrigues, Hemini Machado (2019)
With the intention of analyzing how the class diaries contribute to the formation and professional motivation of the students of the course of Pedagogy, participants of PIBID, this study was carried out with the participation of ten subjects who collaborated with the research and answered the questionnaires. After the data collection, the data was analyzed through a qualitative exploratory study, with the support of Discursive Textual Analysis (DTA). In this movement, three categories emerged: a) Relation theory and practice; b) Improve methodologies in search of new knowledge; c) Intrapersonal feelings. Thus, it was possible to identify that the classroom diary is a tool that contributes to the participation of learners and educators, based on central aspects such as: the collective, the construction of new concepts, reading / writing and reflection. This process was aimed at identifying the motivation for the teacher training to carry out the records in the class diaries, by the students of the Pedagogy course, participants of the PIBID of the years 2011, 2012, 2013 and 2014. From the study carried out, it is possible to observe the change after the experiment to PIBID and the use of the classroom diary tool.